Optimal Design and Verification of a PM Synchronous Generator For Wind Turbines - Cetinceviz, Yucel; Uygun, Durmus; Demirel, Huseyin (Aperta, 2017)
This study reports the analytical computation including performance characteristics under no-load condition in combination with coupled 2D electromagnetic field-circuit analysis of a 4kW direct drive permanent magnet synchronous generator (PMSG) to be used in micro-scale wind turbine applications. The specifications such like stack length, skew and magnet offset of PMSG are optimized by using parametric approach including multi-objective design optimization. It describes the methodology to gain required output performance such as output power, load voltage and maximum efficiency of the wind generator. Based on the optimized design, the model has been exposed to some transient coupled-field circuit analyses based on variable wind flow speed under no-load conditions. In addition to these evaluations; the experimental results verified the effectiveness of the employed simulations model related to finite element methods and analytical studies showing that that the induced voltage at nominal speed and no-load condition is at desired level and results obtained under no-load condition are in good agreement with the analysis and analytical results.